To solve a system of equations using the elimination method, follow these steps:
Step 1: Write down the two equations in the system.
Step 2: Choose a variable to eliminate. Look for a variable that will cancel out when you add or subtract the two equations.
Step 3: Multiply one or both equations by a constant if necessary to make the coefficients of that variable the same.
Step 4: Add or subtract the two equations to eliminate the chosen variable.
Step 5: Solve the resulting equation for the remaining variable.
Step 6: Substitute the value of the remaining variable back into one of the original equations to find the value of the eliminated variable.
Let's try an example:
1) 2x + 3y = 11
2) 3x - 2y = 2
Step 2: We can eliminate the variable y by adding the two equations together.
Step 3: We need to make the coefficient of y the same in both equations. We can do this by multiplying equation (1) by 2 and equation (2) by 3.
(2) 4x + 6y = 22
(3) 9x - 6y = 6
Step 4: Add equations (2) and (3) together:
4x + 6y + 9x - 6y = 22 + 6
13x = 28
x = 28/13
Step 5: Substitute x back into one of the original equations. Let's use equation (1):
2(28/13) + 3y = 11
56/13 + 3y = 11
3y = 143/13
y = 143/39
Therefore, the solution to the system of equations is x = 28/13 and y = 143/39.
solving with elimination practice
1 answer